A Facile Method for the Removal of dsRNA Contaminant from In Vitro-Transcribed mRNA - Baiersdörfer, Markus; Boros, Gábor; Muramatsu, Hiromi; Mahiny, Azita; Vlatkovic, Irena; Sahin, Ugur; Karikó, Katalin (Molecular therapy. Nucleic acids, 2019)
The increasing importance of in vitro-transcribed (IVT) mRNA for synthesizing the encoded therapeutic protein in vivo demands the manufacturing of pure mRNA products. The major contaminant in the IVT mRNA is double-stranded RNA (dsRNA), a transcriptional by-product that can be removed only by burdensome procedure requiring special instrumentation and generating hazardous waste. Here we present an alternative simple, fast, and cost-effective method involving only standard laboratory techniques. The purification of IVT mRNA is based on the selective binding of dsRNA to cellulose in an ethanol-containing buffer. We demonstrate that at least 90% of the dsRNA contaminants can be removed with a good, >65% recovery rate, regardless of the length, coding sequence, and nucleoside composition of the IVT mRNA. The procedure is scalable; purification of microgram or milligram amounts of IVT mRNA is achievable. Evaluating the impact of the mRNA purification in vivo in mice, increased translation could be measured for the administered transcripts, including the 1-methylpseudouridine-containing IVT mRNA, which no longer induced interferon (IFN)-α. The cellulose-based removal of dsRNA contaminants is an effective, reliable, and safe method to obtain highly pure IVT mRNA suitable for in vivo applications.